Energy commitment: a planning of energy carrier based on energy consumption - Dehghani, M.; Montazeri, Z.; Malik, O.P. (Електротехніка і електромеханіка, 2019)
Purpose. Energy consumption is one of the criteria for determining the quality of life in a country. Continued supply of energy and the possibility of long-term access to resources require a comprehensive plan. One of the key issues in the field of energy planning is energy carriers. In this paper, a new theory is introduced to energy network studies for planning of energy carriers called Energy Commitment. In this theory, an appropriate planning is applied for energy carriers based the final energy consumption. Energy carriers are available either naturally or after the energy conversion process. Energy commitment is modeled on an energy network with the presence of electrical energy, gas energy, transportation section, agriculture section, industrial section, residential section, commercial section, and general section. Цель. Потребление энергии является одним из критериев определения качества жизни в стране. Непрерывные поставки энергии и возможность долгосрочного доступа к ресурсам требуют комплексного плана. Одним из ключевых вопросов в области энергетического планирования являются энергоносители. В данной статье в исследования энергетических сетей для планирования энергоносителей вводится новая теория под названием Energy Commitment («энергетическое обязательство»). В этой теории для энергоносителей применяется соответствующее планирование на основе конечного потребления энергии. Энергоносители доступны либо естественным путем, либо после процесса преобразования энергии. Energy Commitment моделируется в энергетической сети с учетом электрической энергии, энергии газа, транспортной отрасли народного хозяйства, сельскохозяйственной отрасли, промышленного сектора экономики, жилищно-коммунального хозяйства, реального сектора экономики и прочих видов экономической активности.